SAT0056 Retro – Study of Reduction of Therapy in Patients with Rheumatoid Arthritis in Ongoing Remission. (9th June 2015) - Haschka, J.; Englbrecht, M.; Hueber, A.J.; Manger, B.; Kleyer, A.; Reiser, M.; Finzel, S.; Tony, H.-P.; Kleinert, S.; Feuchtenberger, M.; Fleck, M.; Manger, K.; et al.
Abstract : Background: Due to improved therapeutic management a steadily increasing number of rheumatoid arthritis (RA) patients reach stable remission of disease. Data on withdrawal of medication after sustained remission are limited, though it is important for economic and safety reasons. The RETRO study represents a real-life study addressing different strategies of reduction of DMARD therapy in RA patients in stable disease remission. Objectives: To prospectively analyze the risk for disease relapses in rheumatoid arthritis (RA) patients in sustained remission, either continuing, tapering, or stopping disease modifying anti-rheumatic drugs (DMARD). Methods: RETRO is a phase 3, multicenter, randomized, controlled, open, prospective, parallel-group trial (EudraCT Number: 2009-015740-42). Patients, fulfilling the ACR/EULAR2010 criteria for RA were enrolled into the study if they were in clinical remission (DAS28-ESR <2.6).Patients on ≥1 conventional and/or biological DMARDs were included and randomized into three treatment arms: Arm 1 (control group) was continuing full-dose conventional and/or biological DMARD treatment; arm 2 was reducing the dose of all conventional and/or biological DMARD treatment by 50% and arm 3 was reducing the dose of all conventional and/or biological DMARD treatment by 50% for 6 months before entirely stopping DMARD. In case of recurrence of disease (DAS >2.6) the original therapy was restarted. Results: 101 patients (61.4% females, 60% ACPA positive, 63% RF positive; 37.6% biologic therapy, 80.2% MTX, 7.9% other DMARDs) finished the one year endpoint: 38 patients in arm 1 (age 55.8±13.9y, disease duration 6.8±5.9y, remission 20.9±16.7mo), 36 patients in arm 2 (age 54.1±13.1y, disease duration 8.6±7.7y, remission 14.5±12.7mo) and 27 patients in arm 3 (age 54.8±12.3y, disease duration 5.6±7.0y, remission 17.6±19.5mo). Of 101 patients, 66.3% were still in remission at 12 mo. Significantly more patients flared in reduction arm 2 (38.9%, c 2 (1)=5.0, p=0.036) and arm 3 (51.9%, c 2 (1)=9.6, p=0.003) compared to control arm 1 (15.8%), while there was no significant difference between the two reduction arms (c 2 (1)=1.1, p=0.443). With multivariate logistic regression ACPA positivity (p=0.03) and treatment reduction (arm2 p=0.01, arm3 p=0.003) were detected as predictors for flares. Conclusions: This study is a prospective real life treatment strategy study investigating the effect of reduction and discontinuation of DMARD therapy in RA patients in stable remission. Presence of ACPA but not RF was the only predictor for recurrence of disease. Disclosure of Interest: None declared